2022
DOI: 10.1002/ecy.3890
|View full text |Cite
|
Sign up to set email alerts
|

Skewness in bee and flower phenological distributions

Abstract: Phenological distributions are characterized by their central tendency, breadth, and shape, and all three determine the extent to which interacting species overlap in time. Pollination mutualisms rely on temporal co‐occurrence of pollinators and their floral resources, and although much work has been done to characterize the shapes of flower phenological distributions, similar studies that include pollinators are lacking. Here, we provide the first broad assessment of skewness, a component of distribution shap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Therefore, although some studies have observed an effect of climate on the flowering durations of individuals or populations (Bock et al, 2014; CaraDonna et al, 2014; Rivest et al, 2021), changes in relative timing of flowering peaks, rather than duration, are probably the main drivers of the variation in temporal isolation that we see in this study (see also Figure 2c,d). The skewness of phenological distributions can also affect overlap (Stemkovski et al, 2022), but we did not test for an effect of spring temperatures on skewness; we assume shifts in peak dates and durations will have larger effects on overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although some studies have observed an effect of climate on the flowering durations of individuals or populations (Bock et al, 2014; CaraDonna et al, 2014; Rivest et al, 2021), changes in relative timing of flowering peaks, rather than duration, are probably the main drivers of the variation in temporal isolation that we see in this study (see also Figure 2c,d). The skewness of phenological distributions can also affect overlap (Stemkovski et al, 2022), but we did not test for an effect of spring temperatures on skewness; we assume shifts in peak dates and durations will have larger effects on overlap.…”
Section: Discussionmentioning
confidence: 99%
“…castes in social insects, or ontogeny more broadly; Nakazawa, 2015). Using phenology as an example, the degree of overlap between interacting species is affected not only by the breadth of their distributions (which has been typically considered) but also by the peaks and shapes (Stemkovski et al., 2023; Figure 3). Therefore, if a plant species' peak flowering coincides with a pollinator species' peak activity, they are more likely to interact than if only the first 5% of the plant species has flowered, given the importance of abundance in determining the probability of two species encountering each other (Bartomeus, 2013; Simmons, Cirtwill, et al., 2019; Vázquez et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although emergent properties can arise from adaptive processes acting on individuals, they can also have important ecological consequences for species communities. For example, population aggregate flowering schedules are sometimes positively skewed with an abrupt start and a long tail of flowering (Blionis et al, 2001; Rabinowitz et al, 1981), which may be an adaptation to enhance pollinator visitation to the population (Stemkovski et al, 2023; Thomson, 1980). Additionally, strong frequency-dependent selection may concentrate flowering within a narrow but synchronous timeframe to attract more pollinators (Rathcke & Lacey, 1985), increase mating opportunities (Ison & Weis, 2017), or prevent interspecific cross-pollination (Fantinato et al, 2018).…”
Section: Introductionmentioning
confidence: 99%